Regulation of cell–cell adhesion in prostate cancer cells by microRNA-96 through upregulation of E-Cadherin and EpCAM. (18th November 2019) - Voss, Gjendine; Haflidadóttir, Benedikta S; Järemo, Helena; Persson, Margareta; Catela Ivkovic, Tina; Wikström, Pernilla; Ceder, Yvonne
Abstract: Prostate cancer is one of the most common cancers in men, yet the biology behind lethal disease progression and bone metastasis is poorly understood. In this study, we found elevated levels of microRNA-96 (miR-96) in prostate cancer bone metastasis samples. To determine the molecular mechanisms by which miR-96 deregulation contributes to metastatic progression, we performed an Argonaute2-immunoprecipitation assay, in which mRNAs associated with cell–cell interaction were enriched. The expression of two cell adhesion molecules, E-Cadherin and EpCAM, was upregulated by miR-96, and potential targets sites were identified in the coding sequences of their mRNAs. We further showed that miR-96 enhanced cell–cell adhesion between prostate cancer cells as well as their ability to bind to osteoblasts. Our findings suggest that increased levels of miR-96 give prostate cancer cells an advantage at forming metastases in the bone microenvironment due to increased cell–cell interaction. We propose that miR-96 promotes bone metastasis in prostate cancer patients by facilitating the outgrowth of macroscopic tumours in the bone. Abstract : Increased levels of miR-96 in prostate cancer bone metastases lead to upregulation of E-Cadherin and EpCAM. This enhances cell–cell adhesion, interaction with osteoblasts and colony formation in prostate cancer cells.